2016
DOI: 10.2147/ndt.s102929
|View full text |Cite
|
Sign up to set email alerts
|

Brain tissue partial pressure of oxygen predicts the outcome of severe traumatic brain injury under mild hypothermia treatment

Abstract: ObjectiveThe aim of this study was to investigate the clinical significance and changes of brain tissue partial pressure of oxygen (PbtO2) in the course of mild hypothermia treatment (MHT) for treating severe traumatic brain injury (sTBI).MethodsThere were 68 cases with sTBI undergoing MHT. PbtO2, intracranial pressure (ICP), jugular venous oxygen saturation (SjvO2), and cerebral perfusion pressure (CPP) were continuously monitored, and clinical outcomes were evaluated using the Glasgow Outcome Scale score.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…[ 25 , 26 ] Regional rSO2 is a commonly used indicator for monitoring rSO2 in clinical practice, which can timely and accurately reflect the balance between oxygen supply and oxygen demand in patients’ brain tissue, and the decrease of rSO2 index indicates insufficient cerebral tissue perfusion. [ 27 ] The study from Ning JQ showed EA stimulation can increase rSO2 levels in patients with diabetes. [ 28 ] The results of this study showed that EA treatment could decrease rSO2 level and increase the score of MoCA and MMSE, indicating that EA treatment could improve the recovery of consciousness after TBI by decreasing cerebral oxygen metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 , 26 ] Regional rSO2 is a commonly used indicator for monitoring rSO2 in clinical practice, which can timely and accurately reflect the balance between oxygen supply and oxygen demand in patients’ brain tissue, and the decrease of rSO2 index indicates insufficient cerebral tissue perfusion. [ 27 ] The study from Ning JQ showed EA stimulation can increase rSO2 levels in patients with diabetes. [ 28 ] The results of this study showed that EA treatment could decrease rSO2 level and increase the score of MoCA and MMSE, indicating that EA treatment could improve the recovery of consciousness after TBI by decreasing cerebral oxygen metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…PbtO 2 monitoring is more helpful in reducing secondary poor brain oxygenation following severe brain trauma, so is more conducive to improving prognosis. Hongtao [ 45 ] and his team administered mild hypothermia treatment (MHT) in 68 severe TBI patients and monitored the changes in PbtO 2 , ICP, SjvO 2 , and CPP. It was found that during MHT, PbtO 2 , SjvO 2 , and CPP increased dramatically, while ICP decreased considerably.…”
Section: Cerebral Blood Oxygen Saturation Monitoring Methodsmentioning
confidence: 99%
“…Monitoring SvO 2 may also reflect the therapeutic effect. For example, Sun et al found the low brain tissue partial pressure of oxygen correlated with a poor outcome of severe TBI with mild hypothermia treatment ( Sun et al, 2016 ). McCredie et al found the treatment of red blood cell transfusion had no measurable impact on cerebral tissue oxygenation in severe TBI ( McCredie et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%